DETERMINATION OF THE OPTIMUM CONDITIONS FOR UREASE EXTRACTED FROM SOME LOCAL PLANTS - Amaal A. H; Sahar I. H; Mohanad J. M-Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
In the current study, Seventeen types of plants commonly used namely (Chickpeas, Tomato, Soybean, Mustard, Baker, Lebbeck, Bean, Sesame, Male Iraqi berries, Female Iraqi berries, Indian berries, Potato, Radish, Legumes, peas, Watermelon, and Phaseolus were obtained and screened for urease activity, among these plants, Sesame was chosen with maximum enzymatic activity, and it had the highest productivity of urease enzyme (1.623 U/mg protein). The optimum extraction ratio represented by 1:10 (W: V) after 90 minutes and 0.8414U/mg protein. Sodium phosphate buffer (0.1 M, pH 7.0) was chosen as the best extraction buffer with specific activity 0.9004U/mg protein.